Sumatriptan Mucoadhesive Buccal Tablet for the Treatment of Migraine - Prajapati, Shivani; Ahmed, Sarfaraz (Journal of Neonatal Surgery, 2025)
In this review , we assessed a buccal sumatriptan formulation specifically for migraine treatment. This abstract provides a concise overview of the key aspects and applications of mucoadhesive buccal tablets of sumatriptan. The primary objective of mucoadhesive buccal tablet is to enhance the bioavailability and therapeutic efficacy of drugs by enabling controlled and sustained release directly into the bloodstream. In this article, we will delve into the concept, development, and applications of mucoadhesive buccal tablet highlighting their key features and benefits in the treatment of migraine.